Generating H2 during the CO2 sequestration in basalt formations - Lizhi Huang; Quansheng Liu; Carl Stefeel; Yiwei Liu; Mengsu Hu; Shimin Liu; Yiheng Zhang; Xuhai Tang (Geomechanics and Geophysics for Geo-Energy and Geo-Resources)
Abstract This work demonstrates the potential of generating H2 and geologically storing CO2 simultaneously in basalt formations. Basalt is able to produce H2 in CO2-saturated water at a rate of 46.68 ppm d−1 under 25 °C, with generation rates leveling off after 6 days. At the reaction temperature of 60 °C, the cumulative hydrogen production of basalt for 5 days reaches 11,960 ppm, and its daily hydrogen production rate is more than 51 times that of 25 °C. The CO2-acidified experiment produced the most H2, presumably due to the pH buffering of the CO2 system. The water–solid reaction interface provided by basalt is essential for H2 production. Scanning electron microscopy (SEM) results show that substantial nano-sized mineral precipitate formed on the basalt surfaces. Electronic microprobe results (EMPA) show that carbonate minerals are formed after the reaction of basalt with CO2 and water under ambient temperature conditions. Thermogravimetric analysis (TG) results show a mineral carbonation efficiency of 4.17% in 3 months. The present experimental results demonstrate the technological feasibility of producing hydrogen for the energy transition while storing CO2 geologically, thus mitigating anthropogenic emissions of a greenhouse gas and also creating revenue for CCS.